APLIKASI PENYEWAAN FASILITAS UMUM PADA BALAI PENGEMBANGAN PENDIDIKAN ANAK USIA DINI DAN PENDIDIKAN MASYARAKAT PROVINSI KALIMANTAN TENGAH BERBASIS WEBSITE - Widiatry Widiatry; Putu Bagus Adidyana Anugrah Putra (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2021)
Department of Early Childhood Education Development and Community Education (BP PAUD and Dikmas) Central Kalimantan Province is the Technical Implementation Unit (UPT) of the Directorate General of Early Childhood Education and Community Education (PAUD and Dikmas) of the Ministry of Education and Culture. Several facilities can be rented out to the public at the agency, such as halls, dormitories, and guest houses. There are still many people who do not know this public facility that can be used. The rental process is still done manually by coming directly or sending a letter of application. In terms of bookkeeping, sometimes there are some data recording errors. Therefore, a website was developed that can help provide information on what public facilities can be used for the public and used to carry out the rental process to help the community make rentals without having to come directly to BP PAUD and Dikmas. Developing this website using the Waterfall software development methodology has stages, namely Requirements Definition, which is done by making Flowcharts. System and Software Design is carried out by making Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD), Implementation and Unit Testing with the programming languages used, namely HTML, PHP, CSS, Bootstrap, Javascript and MySQL and Integration and System Testing. The testing method used is the Blackbox method. Based on the test results, it can be concluded that this website can run according to its function. The final result of this program also shows the achievement of the objectives that have been implemented, such as the presence of several features that are used appropriately according to their use.